Training to Improve English Vocabulary Via Audio-Visual Media For Primary Students of Silo Baru Village Dusun X Asahan District - Marpaung, Agus Salim; Pulungan, Putri Suaidah (Pusdikra Publishing, 2024)
When it is done appropriately, the transition from traditional classroom instruction to technology-based instruction in English language instruction has a lot of potential advantages. A few crucial aspects of its implementation to consider include selecting appropriate technology and emphasizing vocabulary expansion. There is a great chance that training targeted at increasing students' vocabulary following the use of audio-visuals in English language learning will boost their motivation even more. Participants from Silo Baru Village's coastal primary schools will have the chance to learn more about this technology in particular. It is hoped that by using audio-visual media to enhance vocabulary acquisition, students will become more intrinsically motivated as a result of this training activity. It is thought that since kids are really interested in studying, they would be able to concentrate more on improving their mastery of vocabulary in English. It is important to monitor and evaluate the impact of this training, both in terms of increasing vocabulary and in students' learning motivation. The data and feedback obtained from this activity will be key to assessing the effectiveness of audio-visual technology in improving the English language skills of coastal elementary schools in the new silo village of Asahan Regency.